1998
DOI: 10.1212/wnl.51.4.1069
|View full text |Cite
|
Sign up to set email alerts
|

Tourette's syndrome

Abstract: These findings indicate that serotonergic neurotransmission in the midbrain and serotonergic or noradrenergic neurotransmission in the thalamus may be important factors in the expression of TS and may suggest novel targets for treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 7 publications
0
51
2
Order By: Relevance
“…This result is in agreement with a b-CIT SPECT study in patients with Tourette's syndrome (TS), a disorder characterized by chronic tics often accompanied by obsessive-compulsive symptoms (OCD-spectrum disorder). Heinz et al (1998a) found a significant negative correlation between midbrain b-CIT binding and vocal tic severity in these patients. Correlations between b-CIT ratios and OCD severity (Y-BOCS scores) were also calculated in all previously mentioned b-CIT OCD studies.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This result is in agreement with a b-CIT SPECT study in patients with Tourette's syndrome (TS), a disorder characterized by chronic tics often accompanied by obsessive-compulsive symptoms (OCD-spectrum disorder). Heinz et al (1998a) found a significant negative correlation between midbrain b-CIT binding and vocal tic severity in these patients. Correlations between b-CIT ratios and OCD severity (Y-BOCS scores) were also calculated in all previously mentioned b-CIT OCD studies.…”
Section: Discussionmentioning
confidence: 62%
“…However, no significant correlations were found in any of these investigations. Again one must keep in mind that these negative results are most likely dependent upon the heterogeneity of the OCD patients, because not only our study with a homogeneous subtype but also that of Heinz et al (1998a) in TS patients showed significant correlations.…”
Section: Discussionmentioning
confidence: 68%
“…97 There was no overall reduction in serotonin transporter density in patients with TS. The authors suggest that serotoninergic transmission is a modifying, but not causal, factor in the pathogenesis of tics.…”
Section: Serotoninmentioning
confidence: 93%
“…96 In contrast, other investigators using similar techniques in 10 adult patients with TS have shown no difference in the mean ␤-CIT binding compared with control subjects. 97 Studies evaluating dorsal striatal dopaminergic innervation by use of in vivo measures of vesicular monoamine transporter type 2 (VMAT2) binding with the ligand (+)-alpha-[ 11 C] dihydrotetrabenazine showed no differences between eight subjects with TS and 22 age-compatible normal control subjects. 98 These results do not support the concept of increased striatal innervation, but do not exclude an abnormality in the regulation of dopamine release or reuptake.…”
Section: Dopaminementioning
confidence: 99%
“…Studies have shown that TS patients who are resistant to neuroleptics show a reduction in tic severity with risperidone, which has combined 5-HT 2 and D 2 antagonism properties (Bruun and Budman, 1996). A negative correlation has been shown between vocal tics and SERT (Heinz et al, 1998). There are few studies on OCD or TS + OCD that clearly delineate the 5-HT abnormalities, and imaging studies have reported inconsistent results.…”
Section: -Ht and Da Relationshipsmentioning
confidence: 99%